Pengaruh Pengetahuan Pajak, Sistem Administrasi Perpajakan dan Tax Amnesty terhadap Kepatuhan Wajib Pajak: Studi Kasus pada Kantor Pajak Pratama Kota Pekalongan Tahun 2024 - Muhammad Helmi; Lintang Kurniawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Taxpayer compliance is essential for increasing state revenue from taxation. This study aims to analyze the influence of Tax Knowledge, Tax Administration System, and Tax Amnesty on Individual Taxpayer Compliance. A quantitative approach was applied using a survey of 111 registered taxpayers. A validated and reliable questionnaire was used, and data were analyzed using multiple linear regression and classical assumption tests. The results show that Tax Knowledge and the Tax Administration System significantly affect Taxpayer Compliance. Improved understanding and efficient tax systems encourage higher compliance. However, Tax Amnesty has no significant effect, indicating its limited impact on long-term compliance. The study recommends strengthening tax education, developing user-friendly digital systems, and evaluating amnesty policy effectiveness.